Adsorption studies on hydrophobic disperse dye using cellulose derived mesoporous activated carbon. (2022) - Mittal, Nisha; Kaur, Manpreet; Singh, Vasundhara
Abstract: Economically viable and eco-friendly low cost activated carbon (AC) has been synthesized from agricultural waste biomass. Rice straw was taken as starting material and its fractionation was done into major lignocellulosic components cellulose, hemicellulose and lignin. The extracted cellulose was used as a precursor for the synthesis of mesoporous activated carbon. Conversion of cellulose to activated carbon has been done using a biodegradable ionic liquid choline hydroxide as an activating agent followed by annealing at 600 °C in an inert atmosphere. The cellulose derived activated carbon was characterized by Fourier Transform Infrared Spectroscopy (FTIR), X-ray diffraction (XRD), Scanning electron microscope (SEM) and N2 adsorption–desorption isotherm. Further, the synthesized AC was used for the adsorption studies of a disperse dye scarlet RR, predominately found in textile industry wastewater. Optimization in terms of initial concentration, pH, and catalyst loading was done and the results obtained are fitted into Langmuir and Freundlich adsorption isotherm.